Factors Affecting Marketing Knowledge Sharing (MKS):The Case of Iranian Food and Auto Industries - Hamidizadeh, Mohammed Reza; Azizi, Shahriar (Indian Journal of Marketing, 2009)
Knowledge is one of the most cited topics in management literature in recent years. Innovations and Knowledge Management (KM) play key roles in managing and increasing competitive advantages of organizations (Porter, 2001). Knowledge is an organization’s only enduring source of advantage in an increasingly competitive world (Birkinshaw, Holm, Thilenius, and Arvidsson 2000). Knowledge Sharing (KS) plays a critical role in KM because KM improves and strengthens by being shared with others. Although there is huge body of knowledge available on KM but enough information is not available about KS and studies about Marketing Knowledge Sharing (MKS) are scarce. The main reason for searching for effect factors in MKS is this statement from Drucker: every company has only two functions: innovation and marketing. Marketing is a boundary spanning function in a company and relates a company with his customers, competitors and other market elements. Marketing knowledge is a new area in marketing and there have been nascent developments in this stage. In this paper, the authors try to explore factors affecting MKS at a personal and micro level in two selected industries in Iran (including food and home appliance). These two industries are highly competitive in Iran. The authors investigate what personal factors affect KS.